Determination of Fe, Mn, Cu, Zn and Cd after Heat Treatment in some vegetables and Green Bean (Phaseolus vulgaris L.) grown in the Middle Black Sea Region - S Fatma Aygun (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2017)
Background: In this study, Fe, Mn, Cu, Zn and Cd were determined after heat treatment of spinach (Spinacia oleracea L.), leek (Allium porrum L.), green bean (Phaseolus vulgaris L.), lamb's-quarters (Chenopodium album L.) and mad parsley (Oenanthe pimpinelloides L.) grown in Samsun the city, in the Middle Black Sea region. In this way, it has been aimed to contribute to the subject whether boiled liquors are consumable or should be thrown away. Methods: In our study, before heat treatment, vegetables and green bean (Phaseolus vulgaris L.) analyzed as raws material and after heat treatment separately as pomace and pot liquor. Chopped vegetables are washed, dried and then HNO3 and HClO4 are added and them wet ashing method was using. By taking five samples from each vegetable and fruit, the concentration of Fe, Mn, Cu, Zn were determined with Flame AAS, but Cd was determined with voltammetry. This process was also applied to vegetable and green bean pomaces. The content of the heavy metals in pot liqour was determined by standard addition method. Results: The highest metal ion was iron in spinach (135.1, 181.6 mg kg-1) on the other hand the lowest metal content was cadmium in leek (0.007, 0.001 mg kg-1) in raw samples and pomace respectively. In pot liqour the highest metal concentration belonged to iron with a concentration of 22.9 mg kg-1 in spinach (Spinacia oleracea L.) and the lowest metal concentration belonged to cadmium with a concentration of 0.001 mg kg-1 in mad parsley (Oenanthe pimpinelloides L.). Conclusion: As a result of our experiments, although the industrial areas emit some heavy metals to the environment, the heavy metal content of studied vegetables and green bean (Phaseolus vulgaris L.) were not exceeded the literature and WHO values. Especially pot liquors of mad parsley (Chenopodium album L.), green bean (Phaseolus vulgaris L.) and lamb's-quarters (Chenopodium album L.) must be thrown away. On the other hand, boiled pot liqour of spinach (Spinacia oleracea L.) and leek (Allium porrum L.) can be consumed.